2021
DOI: 10.1111/brv.12827
|View full text |Cite
|
Sign up to set email alerts
|

Newborn and elderly skin: two fragile skins at higher risk of pressure injury

Abstract: Skin is a key organ maintaining internal homeostasis by performing many functions such as water loss prevention, body temperature regulation and protection from noxious substance absorption, microorganism intrusion and physical trauma. Skin ageing has been well studied and it is well known that physiological changes in the elderly result in higher skin fragility favouring the onset of skin diseases. For example, prolonged and/or high‐intensity pressure may suppress local blood flow more easily, disturbing cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 251 publications
(561 reference statements)
1
26
0
2
Order By: Relevance
“…In recent years, increased extreme weather and flourished means of chemoradiotherapy have damaged the skin by UV light and chemoradiotherapy drugs. The study confirmed that the skin of chemoradiotherapy patients, newborns, elderly people and long-term outdoor workers were more vulnerable ( 2 , 3 ).…”
Section: Introductionsupporting
confidence: 62%
“…In recent years, increased extreme weather and flourished means of chemoradiotherapy have damaged the skin by UV light and chemoradiotherapy drugs. The study confirmed that the skin of chemoradiotherapy patients, newborns, elderly people and long-term outdoor workers were more vulnerable ( 2 , 3 ).…”
Section: Introductionsupporting
confidence: 62%
“…36,37 Overall, thinning and structural changes of the epidermis contribute to epidermal fragility increasing the risk for injuries such as skin tears. 38 For many years, there are ongoing discussions about ET differences in different ethnic origins and skin types. We found the Caucasian epidermis to be thinner compared to the other ethnic groups in eight of the ten investigated skin areas.…”
Section: Discussionmentioning
confidence: 99%
“…The epidermal thinning is clinically relevant because it is accompanied by an impaired epidermal barrier function, and the change of its viscoelastic properties might explain the susceptibility to develop ageing‐related skin diseases 36,37 . Overall, thinning and structural changes of the epidermis contribute to epidermal fragility increasing the risk for injuries such as skin tears 38 …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, when the morphology of the corneocytes is perturbed, an impaired barrier function is observed, and some skin disorders may arise [9]. Besides not fully developed skin barrier function of neonates and infants [10], their skin has additionally lower mechanical resistance to damage due to thinner epidermis, dermis, and hypodermis with a flatter dermal-epidermal junction [11,12]. Biochemical characteristics also show differences [11].…”
Section: Introductionmentioning
confidence: 99%